Internal Solitary Waves Observed on the Continental Shelf in the Northern South China Sea From Acoustic Backscatter Data - Feng, Yingci; Tang, Qunshu; Li, Jian; Sun, Jie; Zhan, Wenhuan (Frontiers in Marine Science, 2021)
Internal solitary waves (ISWs) are investigated offshore of Guangdong in the northern South China Sea (SCS) using high-frequency acoustic backscatter data of 100 kHz acquired in July 2020. Simultaneous XBT profiles and satellite images are incorporated to understand their propagation, evolution, and dissipation processes in shallow water at depths less than 50 m. The water column structures revealed by acoustic backscatter data and XBT profiles are consistent with a small difference of less than 3 meters. A soliton train with apparent vertical and horizontal scales of ~7 m and 100 m, respectively, is captured three times in 20 hours in the repeated acoustic sections, which provides spatiotemporal constraints to the solitons. The characteristics of ISW phase speeds are estimated from acoustic backscatter data and satellite data and using theoretical two-layer KdV and eKdV models. The acoustically observed phase speed of ISWs is approximately 0.4-0.5 m/s, in agreement with the estimates from both satellite data and model results. The shallow solar-heated water in summer (~10-20 m) lying on the bottom cold water is responsible for the extensive occurrence of ISWs in the study region. ISWs are dissipated at the transition zone between the heated surface water and the upwelled water, forming a wide ISW dissipation zone in the coastal area, as observed from satellites. The acoustic backscatter method could be an effective way to observe ISWs with high resolution in shallow water and thus a potential compensatory technique for imaging the shallow blind zone of so-called seismic oceanography.